The Role of Learning Experiences in the Development of Expertise - Robin S. Grenier (Adult Education Research Conference, 2006)
This study examined the types of learning experiences leading to the development of expertise. A qualitative research approach was employed with twelve participants from a purposeful sampling of four historically themed museums. Analysis revealed learning experiences leading to expertise development included formal training and continuing education and informal and incidental learning.
Keywords: Expertise; museums; adult learning